Blood lactate level in Wistar rats after four and twelve week intermittent aerobic training (Medical Journal of Indonesia, 2013)
Background: Aerobic training can be done not only continuously, but also intermittently. Intermittent aerobic training aimed to get blood lactate level lower than continuous aerobic training. Blood lactate concentration in one of the various factors that determine training performance. However, until recently, little studies about intermittent aerobic training and blood lactate levels have been done. Therefore, this study aimed to measure blood lactate levels in Wistar rats after 4 and 12 weeks of intermittent aerobic training. Methods: 16 Wistar rats were divided into two groups, control and aerobic group. Every group was divided into two subgroups, 4-week and 12-week subgroup. Aerobic group performed training using T-6000 treadmill with a speed of 20 m/minute for 20 minutes, with resting period for 90 seconds every 5 minute. Measurements of lactate level was done with L-lactate (PAP) Randox kit (LC2389). Results: Blood lactate level in the 4-week aerobic group was 2.11 mmol/L, while that of the 4-week control group was 1.82 mmol/L (p > 0.05). Meanwhile, lactate level in 12-week aerobic group was 1.71 mmol/L (p < 0.05), and significantly lower than in 12-week control group, which was 3.03 mmol/L. Conclusion: This study showed that lactate level after 12-week intermittent aerobic training was the lowest compared to 4-week intermittent aerobic and 12-week control group.